2015
DOI: 10.1186/s12986-015-0058-6
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein CIII overexpression exacerbates diet-induced obesity due to adipose tissue higher exogenous lipid uptake and retention and lower lipolysis rates

Abstract: BackgroundHypertriglyceridemia is a common type of dyslipidemia found in obesity. However, it is not established whether primary hyperlipidemia can predispose to obesity. Evidences have suggested that proteins primarily related to plasma lipoprotein transport, such as apolipoprotein (apo) CIII and E, may significantly affect the process of body fat accumulation. We have previously observed an increased adiposity in response to a high fat diet (HFD) in mice overexpressing apoCIII. Here, we examined the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
2
9
0
1
Order By: Relevance
“…Here, we confirmed that HFD consumption induces insulin resistance more severely in apoCIII mice than in NTg mice, as shown by the simultaneous glucose intolerance and increased gluconeogenesis that developed in the former group. We also confirmed a recent find from our group that apoCIII overexpression aggravates diet-induced obesity [26]. We have previously shown that apoCIII mice exhibit normal glucose homeostasis and insulin secretion when fed a normal diet, and these parameters were disturbed following acute increases in plasma FFA levels induced by heparin [27] or HFD consumption [28].…”
Section: Discussionsupporting
confidence: 90%
“…Here, we confirmed that HFD consumption induces insulin resistance more severely in apoCIII mice than in NTg mice, as shown by the simultaneous glucose intolerance and increased gluconeogenesis that developed in the former group. We also confirmed a recent find from our group that apoCIII overexpression aggravates diet-induced obesity [26]. We have previously shown that apoCIII mice exhibit normal glucose homeostasis and insulin secretion when fed a normal diet, and these parameters were disturbed following acute increases in plasma FFA levels induced by heparin [27] or HFD consumption [28].…”
Section: Discussionsupporting
confidence: 90%
“…Numerous genes have been shown to modulate adiposity during recent decades. Among them, genes encoding proteins primarily related to plasma lipoprotein transport have been associated with body fat accumulation, such as apolipoprotein (apo) CIII and apo E [13][14][15][16]. In a previous work, we demonstrated that CETP expression attenuated diet-induced obesity in hypertriglyceridemic apo CIII-overexpressing mice [17].…”
Section: Introductionmentioning
confidence: 94%
“…Diet encouraged over-expression of human LPL hinders the diet-induced obesity in the skeletal muscles of transgenic mice [ 614 , 615 ]. The ratio of carbohydrate: fat oxidation remains unperturbed indicated in the observation of constant Respiratory Quotient (RQ; moles of CO 2 production per mole of Oxygen consumed) [ 616 ]. A relationship between the RQ and body weight revealed in previously published analysis.…”
Section: Industrial Applications Of Lipasesmentioning
confidence: 99%